1979
DOI: 10.3402/tellusa.v31i1.10406
|View full text |Cite
|
Sign up to set email alerts
|

Calculations of free atmospheric shortwave spectral characteristics over the desert (from the CAENEX-70 data)

Abstract: This report presents a summary of a joint Soviet/American exchange program to compare calculations with observations in the real atmosphere, in order to determine and study the diabatic processes that are important for tropospheric energetics. The primary purpose of the present investigation was to determine the effect of aerosols upon radiation characteristics in the real atmosphere. Spectral measurements of the radiation field as a function of height have been made in 0.01 pm increments from 0.4 pm to 0.9 pm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1982
1982
2006
2006

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…The size of soot particles produced by combustion processes ranges from the submicron to visible (Finfer, 1967), though particles with radii larger than a few microns will quickly fall out. As for hematite particles, Kondratyev et al (1979) found their sizes to be about 0.1*m; however, the existence of hematite particles in the supermicron size range is also reported (Klappenbach and Goranson, 1979). In spite of these reports, our knowledge of the size distribution of these absorbing particles is still very incomplete.…”
Section: Model Size Distribution O F Mixed Particlesmentioning
confidence: 80%
See 1 more Smart Citation
“…The size of soot particles produced by combustion processes ranges from the submicron to visible (Finfer, 1967), though particles with radii larger than a few microns will quickly fall out. As for hematite particles, Kondratyev et al (1979) found their sizes to be about 0.1*m; however, the existence of hematite particles in the supermicron size range is also reported (Klappenbach and Goranson, 1979). In spite of these reports, our knowledge of the size distribution of these absorbing particles is still very incomplete.…”
Section: Model Size Distribution O F Mixed Particlesmentioning
confidence: 80%
“…In the real atmosphere, however, such microphysical processes as coagulation, adsorption of reactive gases onto the particle surface, and incorporation in the cloud forming process eventually lead to a mixed nature of individual aerosol particles (i.e., internal mixing becomes predominant). From the analysis of the CAENEX data, Kondratyev et al (1979) suggested a possibility that hematite was embedded within other less absorbing particles in the atmosphere. The absorption property of an inhomogeneous particle which contains both absorbing and nonabsorbing substances may be different from that of a homogeneous particle composed of the absorbing substance only; therefore it is of interest to inquire into the optical properties of these inhomogeneous aerosol particles.…”
Section: Introductionmentioning
confidence: 99%